The Influence of Self Assessment System, Training Methods, and Training Materials on Tax Volunteers Performance - Fadia Agustina Hanum; Achmad Wicaksono; Chairil Anwar; Dian Fahriani (Commodities, Journal of Economic and Business, 2026)
The purpose of this study is to determine how the self Assessment system, training methods, and training materials affect the performance of tax volunteers at the Faculty of Economics, Nahdlatul Ulama University, Sidoarjo. Tax volunteers at the Faculty of Economics, Nahdlatul Ulama University, Sidoarjo for the 2024–2026 period are the population in this study. All population members were selected as samples using the saturated sampling method, which is a non-probability sampling technique. A total of 84 students from the Faculty of Economics at Nahdlatul Ulama University Sidoarjo are registered as tax volunteers for the 2024–2026 period. Each respondent completed a Likert scale questionnaire (1–5) to collect primary data. SPSS software was used throughout the data analysis process. According to the research findings, the Self-Assessment System, Training Methods, and Training Materials all have a simultaneous effect on volunteer performance. The Self-Assessment System variable has a significant effect on tax volunteer performance, while the Training Methods and Training Materials factors do not have a significant effect.